OCORRÊNCIA DE GONIPTERUS SCUTELLATUS GYLLENHAL (COLEOPTERA: CURCULIONIDAE) EM PLANTAÇÕES DE EUCALIPTO NO ESTADO DO ESPÍRITO SANTO - Wilcken, C.f. [UNESP]; Oliveira, N.c. De [UNESP]; Sartório, R.c.; Loureiro, E.b.; Bezerra, N.; Rosado, G.h. (Instituto Biológico, 2021)
The eucalyptus snout beetle Gonipterus scutellatus Gyllenhal was found in Espirito Santo State, Brazil, attacking clonal plantations of Eucalyptus urophylla x E. grandis (hybrid “urograndis”). The presence of this species in Brazil has been known since 1979, with a geographical distribution restricted to Brazil’s South and São Paulo State. The pest’s introduction to the state of Espírito Santo was probably accidental and its occurrence has been limited to the central region of the state. Field surveys did not detect the egg parasitoid Anaphes nitens (Hymenoptera: Mymaridae), which is the main natural enemy of G. scutellatus.

O gorgulho do eucalipto Gonipterus scutellatus Gyllenhal foi encontrado no Estado do Espírito Santo atacando plantações clonais de Eucalyptus urophylla x E. grandis (híbrido “urograndis”). Essa espécie de gorgulho é conhecida no Brasil desde 1979, tendo sua distribuição geográfica restrita aos estados da região Sul e São Paulo. A introdução do inseto no Estado do Espírito Santo foi provavelmente acidental e sua ocorrência tem se limitado à região central do Estado. Nos levantamentos de campo não foi detectado o parasitóide de ovos Anaphes nitens (Hymenoptera: Mymaridae), que é o principal inimigo natural do gorgulho do eucalipto.
GONIPTERUS SCUTELLATUS GYLLENHAL (COLEOPTERA: CURCULIONIDAE) OCCURRENCE IN EUCALYPTUS PLANTATIONS IN ESPÍRITO SANTO STATE, BRAZIL
Keywords: Forest pest; eucalyptus snout beetle; Eucalyptus; forest protection; Praga florestal; gorgulho do eucalipto; Eucalyptus; proteção florestal